Spatial Accessibility of Community-Based Child-Rearing Health Consultation Services in a Mixed Urban-Rural Municipality in Japan: An Open-Data GIS Analysis - Kumakura, Ryota; Takahashi, Yutaro; Horiike, Ryo; Omote, Shizuko; Okamoto, Rie (Journal of Rural Community Nursing Practice, 2026)
Background: Community-based child-rearing support services are essential for promoting equitable access to maternal and childcare. However, spatial inequities in accessibility may persist in municipalities that encompass both urban and rural areas. The expansion of open government data enables transparent evaluation of spatial accessibility in local health planning. Purpose: This study aimed to evaluate the spatial accessibility of community-based child-rearing health consultation services in Kanazawa City and to demonstrate a reproducible open-data GIS framework applicable to municipal-level child health planning. Methods: A cross-sectional spatial analysis was conducted using consultation site locations and population data in 250-m grid-cells for children aged 0–2 years. Network-based service areas were generated using predefined walking (900 m and 1,800 m) and driving (7.5 km and 15 km) distances. Both area-based coverage and population-weighted coverage within these service areas were calculated. Results: Forty-nine consultation sites were identified. At the 1,800-m walking-distance threshold, service areas covered 76.1% of child-inhabited residential grid areas and 86.5% of the population aged 0–2 years, indicating higher population-weighted coverage than area-based coverage. In contrast, driving-distance service areas encompassed nearly all residential grid areas and virtually all children within the municipality. Conclusions: Pedestrian accessibility to child-rearing consultation services varies within this mixed urban–rural municipality, leaving geographically dispersed areas underserved despite relatively high population-weighted coverage in urban districts. Open-data-driven spatial analysis using both area-based and population-weighted indicators provides a scalable framework for identifying spatial inequities and supporting evidence-based municipal child health planning